ANTIMONOUS ACID PROTONATION/DEPROTONATION EQUILIBRIA IN HYDROTHERMAL SOLUTIONS TO 300 °C - Zakaznova-Herzog V.P.; Seward T.M. (My University, 2006)
The ultraviolet spectra of dilute aqueous solutions of antimony (III) have been measured from 25 to 300 °C at the saturated vapour pressure. From these measurements, equilibrium constants were obtained for the following reactions:{A formula is presented}for which pK1 (antimonous acid) decreases from 11.82 to 9.88 over a temperature range from 25 to 300 °C and{A formula is presented}for which log Ka initially decreases from 1.38 at 22 °C with increasing temperature up to 100 °C but then increases until it reaches a value of log Ka = 1.8 at 300 °C. Unionised antimonous acid, H3SbO30, will be the dominant species responsible for antimony transport in low sulphur geothermal fluids in the Earth's crust. In hydrothermal fluids having a high magmatic input, the low pH environment will also encourage the stability of the protonated H4SbO3+ species. © 2006 Elsevier Inc. All rights reserved.